Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Wisatawan pada Bali Jungle Swing - Dewi, Ni Kadek Mas Arisma; Putu Kawiana, I Gede; Oktarini, Luh Nik (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study is to determine the effect of service quality and price on tourist satisfaction on Bali Jungle Swing. This research was conducted on Bali Jungle Swing which is located at Jl. Tanggayuda, Bongkasa, Abiansemal District, Badung Regency. The object of this study is the field of marketing, namely the Effect of Service Quality (X1) and Price (X2) on Tourist Satisfaction (Y). The total population in this study was 409 Bali Jungle Swing tourists. From the calculation of the slovin formula, the number of samples to be studied is 96 respondents who are Bali Jungle Swing tourists. The research design used in this study was an associative design. The sampling method used in this study is the non-probability sampling method. The types of non-probability sampling used are pusposive sampling and convenience sampling. Data collection methods in this study are observation, literature study, interviews, documentation and questionnaires. The test techniques used in this study are research instrument tests, classical assumption tests, multiple linear regression analysis, t test analysis and F test. Based on the results of data analysis and discussion, the conclusions of the research carried out at Bali Jungle Swing are as follows: 1) Service quality has a positive and significant effect on tourist satisfaction at Bali Jungle Swing. 2) Price has a positive and significant effect on tourist satisfaction on Bali Jungle Swing. 3) Service quality and price simultaneously have a positive and significant effect on tourist satisfaction in Bali Jungle Swing. The advice given is that Bali Jungle Swing leaders should maintain the quality of cleanliness of the facilities available, add new tourist experiences and promote promos, discounts or increase the types of products and services and facilities available at Bali Jungle Swing